2018
DOI: 10.1111/cdev.13109
|View full text |Cite
|
Sign up to set email alerts
|

Can't Ignore—Distraction by Task‐Irrelevant Sounds in Early and Middle Childhood

Abstract: Attention control abilities are relevant for learning success. Little is known about the development of audio-visual attention in early childhood. Four groups of children between the ages of 4 and 10 years and adults performed an audio-visual distraction paradigm (N = 106). Multilevel analyses revealed increased reaction times in a visual categorization task when task-irrelevant novel sounds were presented, demonstrating involuntary distraction of attention. This distraction effect decreased with age and signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 57 publications
3
53
1
Order By: Relevance
“…For example, this could be done by using novel sounds that are not repeated throughout the experiment (Berti, 2012; Escera et al, 1998; Wetzel, Schröger, & Widmann, 2016; cf. Wetzel et al, 2013) or by studying children or elderly populations who can show greater distraction (Andrés et al, 2006; Gumenyuk et al, 2001; Gumenyuk, Korzyukov, Alho, Escera, & Näätänen, 2004; Leiva, Andrés, Servera, Verbruggen, & Parmentier, 2016; Leiva et al, 2015a; Wetzel, Scharf, & Widmann, 2018; Wetzel et al, 2016; cf. Leiva et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, this could be done by using novel sounds that are not repeated throughout the experiment (Berti, 2012; Escera et al, 1998; Wetzel, Schröger, & Widmann, 2016; cf. Wetzel et al, 2013) or by studying children or elderly populations who can show greater distraction (Andrés et al, 2006; Gumenyuk et al, 2001; Gumenyuk, Korzyukov, Alho, Escera, & Näätänen, 2004; Leiva, Andrés, Servera, Verbruggen, & Parmentier, 2016; Leiva et al, 2015a; Wetzel, Scharf, & Widmann, 2018; Wetzel et al, 2016; cf. Leiva et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, few studies have investigated these hypotheses. Some electroencephalographic and behavioral works suggest that the increased behavioral distraction in children results from a delayed reorientation of attention to the task at hand (Ruhnau et al, 2010;Wetzel et al, 2018). However, inconsistent results have been reported (Wetzel & Schröger, 2014) and further electro-or magnetoencephalographic studies during development will help our understanding of the brain mechanisms underlying increased distractibility.…”
Section: Impact Of Distracting Information On Children Behaviormentioning
confidence: 98%
“…Concerning distraction, previous developmental studies using oddball paradigms provided contradictory results regarding changes in the deviance distraction effect between children and adults. Some studies found that the deviance distraction effect decreases with age, with mature performance around the age of DISTRACTIBILITY FROM CHILDHOOD TO ADULTHOOD 32 10 (Wetzel et al, 2006(Wetzel et al, , 2018Wetzel, Schröger, et al, 2016;Wetzel & Schröger, 2007), while other works found no effect of age (Horváth et al, 2009;Leiva et al, 2016;Ruhnau et al, 2013;Wetzel et al, 2009). This discrepancy can result from differences in the tested age-ranges and from the dissociation between the distracting event and the target.…”
Section: Impact Of Distracting Information On Children Behaviormentioning
confidence: 99%
“…For example, poor performance during childhood could ensue from an immature voluntary orienting subsystem (Mezzacappa, 2004;Reis Lellis et al, 2013) leading to difficulties in sustaining attention (Betts et al, 2006;Kanaka et al, 2008;Lin et al, 1999;Thillay et al, 2015) or in inhibiting distractors (Booth et al, 2003;Howard et al, 2014), or from an immature involuntary orienting subsystem responding more strongly to irrelevant events (Wetzel et al, 2006(Wetzel et al, , 2016(Wetzel et al, , 2018Wetzel & Schröger, 2007). Another possibility is that protracted maturation of the alerting system leads to general over or under-arousal (Hernes et al, 2002;Lansink & Richards, 1997;Wetzel et al, 2015).…”
Section: Attention In Childrenmentioning
confidence: 99%
“…These measures improve from school age to adulthood (Olesen et al, 2007;Wetzel et al, 2006;Wetzel & Schröger, 2007), suggesting a reduction in distractibility with age. To our knowledge, only one study has investigated the distraction effect on behavioral performance in preschool-aged children using an audio-visual oddball task, and results suggest that the deleterious effect of distraction progressively decreases during the preschool period, with a critical developmental step between ages four and five (Wetzel et al, 2018).…”
Section: Distraction In Childrenmentioning
confidence: 99%